SOME DENSITY PROFILES OF AN INHOMOGENEOUS SCHRöDINGER EQUATION - T. B. Prayitno (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
We provide some density profiles of an inhomogeneous Schrödinger equation by giving some available functions representing the inhomogeneous term. The inhomogeneous Schrödinger equation, which is achieved by reducing a set of two-coupled Gross-Pitaevskii equations, describes a motion equation of a weakly outcoupled atom laser inside the condensate zone. In this case, to attain the density profile we use the separation of variables in order to simplify our calculation. Keywords: density profile, atom laser, Schrödinger equation.